2013
DOI: 10.1159/000353762
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Familial Predisposition Are Significant Determining Factors of an Adverse Metabolic Profile in Young Patients with Congenital Adrenal Hyperplasia

Abstract: Background/Aims: Glucocorticoid (GC) therapy is known to predispose to an adverse metabolic profile. Therefore, we investigated the prevalence of obesity and metabolic syndrome (MetS) in young patients with congenital adrenal hyperplasia (CAH) and to correlate this prevalence with GC treatment and family history. Methods: The study population consisted of 33 young CAH patients who received cortisone acetate during their growth periods; those who were salt wasters also received fludrocortisone. Obesity was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Our longitudinal study's findings of increased overweight and obesity in children with CAH is consistent with high BMI percentiles found by some prior cross‐sectional studies but differs from others which did not find increased BMI percentiles . However, none of these studies examined differences in obesity status at different age intervals or used BMI‐for height‐age effects, independent of BMI‐for‐age ranking.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our longitudinal study's findings of increased overweight and obesity in children with CAH is consistent with high BMI percentiles found by some prior cross‐sectional studies but differs from others which did not find increased BMI percentiles . However, none of these studies examined differences in obesity status at different age intervals or used BMI‐for height‐age effects, independent of BMI‐for‐age ranking.…”
Section: Discussionsupporting
confidence: 87%
“…Body composition of children with CAH is an emerging area of focus, and recent data indicate that body mass index (BMI) and/or fat mass is elevated in children and adults with CAH . In normal growth, BMI increases rapidly in infancy and peaks at around the first year of life.…”
Section: Introductionmentioning
confidence: 99%
“…Medes-dos-Santos et al (2011) concluded in their cross sectional, retrospective study that height in these children was similar to unaffected children of the same age, yet children with CAH had higher body fat, which tended to be visceral. Similarly, Moreira et al (2013) found that children with CAH presented with a higher prevalence of obesity and metabolic syndrome, but child weight was not correlated with glucocorticoid treatment. Cetinkaya and Kara evaluated the effects of glucocorticoid doses on bone mineral density in their 2011 study and found that children with CAH had higher BMIs than controls.…”
Section: Resultsmentioning
confidence: 95%
“…Obesity was found to be a significant problem in children with CAH (Volkl, Simm, Beier, & Dorr, 2006; Mendes-dos-Santos et. al, 2011; Cetinkaya & Kara, 2011; Moreira et al, 2013). Medes-dos-Santos et al (2011) concluded in their cross sectional, retrospective study that height in these children was similar to unaffected children of the same age, yet children with CAH had higher body fat, which tended to be visceral.…”
Section: Resultsmentioning
confidence: 99%
“…Glucocorticoid dose, advanced maturation of the bone age and parental obesity contribute to increased BMI-SD score (SDS) in children and adolescents with CAH 27 28. An early ‘adiposity rebound’, defined as the age at which the physiological decrease in BMI reverses, has also been described in children with CAH 29.…”
Section: Cardiovascular and Metabolic Risk Profile In Children And Yomentioning
confidence: 99%